The Effects of Ergonomic Design on Health Professionals and Patient Safety - İzzet Aydemir; Gülbiye Yenimahalleli Yaşar (Association of Nurse Managers, 2017)
In health organizations, patient and professional safety are influenced by many factors. One of the most important of these factors and often ignored is ergonomic. As defined designing of system, hardware, environment, tools and equipment in accordance with human, ergonomics, can be expressed as a discipline and allows us to understand the interaction between human behavior, system design and safety. Hence, the aim of the study is to examine the potential impact of the ergonomic design on healthcare professionals and patient safety in hospital setting in the view of literature. Before examination, the historical and conceptual development of ergonomics is discussed and then, emphasized on the importance of ergonomic principles in detail. Afterwards, the impact of ergonomic design in hospital environment and the tools used on the health professionals and patient safety is addressed. At the end of the study, with the given national and international studies related to ergonomic interventions in hospitals, understanding of the research objectives have been consolidated.